Phytochemical Screening of Bruguiera cylindrica Extracts and Pathogenic Antibacterial Activities - Vittaya, Luksamee; Charoendat, Uton; Janyong, Sittichoke; Leesakul , Nararak (Recent Science and Technology, 2020)
Bruguiera cylindrica is a mangrove plant in the Rhizophoraceae family which founded in tropical regions. The dried samples of bark, leaf, pod and twig of B. cylindrica were collected and were macerated with methanol. Crude extract of each parts was determined the phytochemical screening and antibacterial activity with the aquatic pathogenic bacteria, Streptococcus agalactiae SAAQ001, Aeromonas hydrophila AHAQ001, Vibrio harveyi VHAQ001 and V. parahemolyticus by hole-plate diffusion method. Most of the plant extracts showed a wide range of antibacterial activity against gram-positive and gram-negative bacteria. In addition, minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) were investigated. The results showed that the leaf and twig extracts of B. cylindrica had the lowest MIC/MBC to S. agalactiae. Phytochemical screening revealed that the B. cylindrica extracts contained a rich source of various phytochemical such as anthraquinone, terpenoids, flavonoids, saponins, phenolics and alkaloids. Terpenoid especially founded in leaf and twig supported antibacterial activity. The results presented here suggested that the presence of bioactive substances from B. cylindrica extracts was the factors responsible for bioactivity against the chosen bacterial pathogens. Also, B. cylindrica was a potential source of biologically active compounds that could be used to develop natural and bioactive pharmaceutical products against bacterial pathogens in aquatic animals.